FLACTUATING RELATIONS BETWEEN IRAN AND THE IRAQI KURDISTAN REGIONAL GOVERNMENT SINCE 1958 - Koç, Engin (Igdir University, 2021)
Bu makale, İran ve Irak Kürdistan Bölgesel Hükümeti (IKBY) arasındaki inişli çıkışlı ilişkileri incelemektedir. İranlı siyasetçiler ve Iraklı Kürtler, uzun yıllar Bağdat üzerinden inşa edilen pragmatik ilişkilere sahipti. Bununla birlikte, General Abdulkerim Kasım darbesine kadar ayrılıkçı Kürt hareketleri hem İran hem de Irak tarafından ortak tehdit olarak algılandı. 1958 Irak darbesinden sonra Kürtler her iki devlet tarafından birbirlerini zayıflatmak amacıyla sürekli kullanıldı. İran ve Iraklı Kürtler arasındaki ilişkiler 1991 yılındaki I. Körfez Savaşı'ndan günümüze dramatik bir şekilde değişti. 2003 yılında ABD'nin Irak'ı işgal etmesinden sonrası İran'ın etkisi sadece Bağdat'ta değil aynı zamanda da Erbil'de de arttı. Bununla beraber, IKBY'nin bağımsızlık referandumuna gitme kararından sonra İran, IKBY'ye baskı yaparak Erbil'i Türkiye, Irak ve Suriye ile birlikte izole etmeye çalıştı. Tahran, kendi sınırlarındaki İran Kürdistan Demokrat Partisi ve PJAK gibi Kürt bölücü gruplardan algıladığı tehdit nedeniyle bağımsız bir Kürt devleti görmek istememektedir. Bu çalışma, İran ve Irak Kürtleri arasında çatışma ve işbirliği nedenlerini analiz etmekle birlikte, 1979 İran Devrimi, DAEŞ terörünün bölgede güçlenmesi ve 2017 bağımsızlık referandumunun ilişkileri nasıl etkilediğini irdelemektedir.

This paper examines the up and down bilateral relations between Iran and the Iraqi Kurdistan Regional Government (KRG). The Iranian politicians and Iraqi Kurds have had pragmatical relationships independent from Baghdad for many years. However, separatist Kurdish movements were seen as a joint target by both Iran and Iraq until General Abdulkarim Qasim’s coup. Since the coup in Iraq in 1958, the Kurdish issue has been used against each other by two sides. The relationship between the Iranian and Iraqi Kurds has changed dramatically since the first Gulf War in 1991. However, since the 2003 invasion of Iraq by the USA, Iran’s influence has been growing, not only in Baghdad, but also in Erbil. Meanwhile, after the KRG’s decision to hold a referendum on independence, Iran put pressure on the KRG and tried to isolate Erbil, as Turkey, Iraq, and Syria did. Tehran is not willing to let an independent Kurdish state be established near its borders because of Iran’s local Kurdish secessionist groups, such as the Democratic Party of Iranian Kurdistan and PJAK. This study analyzes the reasons for the conflict and cooperation between the Iranian regime and Iraqi Kurds and focuses on how the Iranian revolution in 1979, the ISIL terrorism and the independence referendum held in 2017, have effected their relations.
FLACTUATING RELATIONS BETWEEN IRAN AND THE IRAQI KURDISTAN REGIONAL GOVERNMENT SINCE 1958